Implementasi Sistem Data Mining Untuk Menentukan Stock Accuracy Pada Warehouse PT Coca-Cola Amatil Indonesia Cibitung–Plant - Hendarman Lubis; Dwi Budi Srisulistiowati (STMIK Budi Darma, 2020)
Abstract−Data Mining is a process of extracting data or filtering data that utilizes large data sets through a series of processes to obtain information that stands out from the data. PT. Coca-Cola Amatil Indonesia Cibitung-Plant has one of the largest warehouse in Indonesia exactly warehouse mega distribution center (DC). With ±32000 m2 warehouse area or equivalent to ±30000 Pallets. To maintain the accuracy of the stock in the warehouse of course required a good system in order to support the operational activities in the warehouse, one way to maintain the accuracy of stock in the warehouse is to do the overall product calculation in the warehouse (Stock Opname), in order to know the accuracy data in the system with the physical stock in the warehouse. With the data transactions stored in the database, sometimes the transaction data is only on leave to accumulate without any further action, then make the information system that manages the data to dig information by data mining techniques.